Cu(OH)x: Clay Catalyst Promoted Synthesis of 4,5-dihydro-1,2,4-oxadiazole at Room Temperature - Dar, Bashir Ahmad; Zaheer, Zahed; Fatema, Samreen; Farooqui, Mazahar (Orbital: The Electronic Journal of Chemistry, 2017)
An easy and efficient scheme is described designed for the preparation of 4,5-dihydro-1,2,4-oxadiazole using recyclable Cu(OH)x-Clay heterogeneous catalyst at room temperature. The cyclo-addition reaction is carried out between imine and oxime using an easy protocol where nitrile oxides are produced in-situ from aldoximes and reacted with imines to construct 1,2,4-oxadiazolines in good yield and tremendous purity. Cu(OH)x-Clay catalyst shows excellent catalytic activity for the formation of 1,2,4-oxadiazole. The technique is practically uncomplicated, inexpensive, and excellent with wide range of functional group tolerance to generate structurally different 1,2,4-oxadiazoles. The prepared catalyst was investigated by XRD and SEM techniques. The final products of synthesized compound were characterized by FTIR, NMR spectroscopy and mass spectrometry. DOI: http://dx.doi.org/10.17807/orbital.v9i5.1062